Effects of adhesive types and structural configurations on shear performance of laminated board from two Gigantochloa bamboos - Mohd Yusof, Norwahyuni; Md Tahir, Paridah; Lee, Seng Hua; Anwar Uyup, Mohd Khairun; James, Redzuan Mohammad Suffian; Osman Al-Edrus, Syeed Saifulazry; Kristak, Lubos; Reh, Roman; Lubis, Muhammad Adly Rahandi (MDPI, 2023)
Semantan (Gigantochloa scortechinii) and beting (Gigantochloa levis) bamboo are the two Malaysian bamboo that are suitable to be converted into laminated bamboo boards. One of the main criteria for laminated board is its good bondability, which is determined by shear performance. The shear performance of laminated board is influenced by several factors such as the species used, adhesive types and lamination configurations. Therefore, in this study, laminated bamboo boards were produced using Semantan and Beting bamboo bonded with phenol–resorcinol–formaldehyde (PRF) and polyurethane (PUR) adhesives. Different configurations (lay-up patterns and strip arrangements) were used during the consolidation of the laminated boards. The bamboo strips were arranged in three different arrangements, namely vertical, horizontal and mixed, and then assembled into a three-layered structure with two lay-up patterns, which are perpendicular and parallel. Shear performances, such as shear strength, bamboo failure and delamination of the boards, were evaluated. The results revealed that the adhesive type and lay-up pattern were the most influential factors on the shear performance. PRF-bonded laminated bamboo boards outperformed PUR-bonded laminated bamboo boards in terms of shear strength and bamboo failure but PUR bonding had better bond durability as indicated by its low delamination. Boards laminated parallelly significantly outperformed those bonded perpendicularly. As for strip arrangement, PRF-bonded laminated boards were less influenced by it compared to PUR-bonded laminated boards. The results suggested that PRF is a better adhesive for bamboo lamination due to its higher shear performance and more consistent performance across structural configurations (lay-up patterns and strip arrangements).